Tunable sub-threshold current firing via insulator-to-metal transition enabled by lithographic nanochannels for neuromorphic applications - Kumar, Mohit; Lee, Jinchan; Seo, Hyungtak (Applied Materials Today, 2024)
The electric field-driven insulator-to-metal transition (IMT) offers a promising platform for developing controllable, futuristic neuromorphic nanoelectronics. However, the volatile nature of IMT, typically stimulated by a specific threshold voltage, limits its potential use primarily to switch-like applications. To broaden its applications, including in-material data processing, achieving on-demand IMT activation with dynamic memory capability is essential. This study demonstrates on-demand modulation of IMT behavior using spatially confined VO2 nanochannels, designed by local probe lithography. This approach enables the integration of ultrafast (∼180 ns) volatile switches (on/off ratio >103) and memory storage, from short- to long-term, in a single device. Notably, the threshold voltage was effectively reduced from 5.6 V to 2.8 V by precisely modulating the width of spatially embedded VO2 nanochannels. The observed memory behavior is attributed to persistent metallic domains and preferential IMT along these channels, as confirmed by optical and Kelvin probe force microscopy. Furthermore, the ability to classify input patterns, even in the presence of noise, was demonstrated using interconnected coplanar nanochannels by leveraging the short-term memory characteristics of the IMT. This report marks a significant step towards on-demand nanoscale manipulation of the IMT dynamics, laying the groundwork for ultrasmall, high-speed, and energy-efficient conventional and neuromorphic nanoelectronics.
Keywords: Dynamic memory; Insulator-to-metal transitions; ITS applications; Nano channels; Neuromorphic; On demands; Site-specific; Subthreshold current; Tunables; Voltage limits; Classification; Dynamic memory; Insulator-to-metal transition; On-demand; Site-specific